1989
DOI: 10.1364/ao.28.001701
|View full text |Cite
|
Sign up to set email alerts
|

Modulation transfer function and quantum efficiency correlation at long wavelengths (greater than 800 nm) in linear charge coupled imagers

Abstract: The spectral modulation transfer function (MTF) of several architecturally identical commercial linear silicon charge coupled imagers (CCIs) was measured and compared to an MTF theory that included the effects of detector aperture and lateral diffusion in one dimension. A successful match between experimental data and theory was possible for proper choices of the detector aperture function and minority carrier lifetime. Long-wave (> 800-nm) MTF and spectral quantum efficiency (QE) data were very well correlate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1990
1990
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…Equation (4b) assumes uniform collection sensitivity across the (rect function) aperture, though the model allows for more complex aperture models, e.g., a trapezoidal function. 42 The distribution of secondary quanta computed at all possible locations in the x domain (taking y = 0 for simplicity) is shown in Fig. 1(C), where the probability distribution (vertical axis) is shown as an intensity map at each x location (horizontal axis) about the point of interaction.…”
Section: A a Cascaded Systems Model For Pcdsmentioning
confidence: 99%
“…Equation (4b) assumes uniform collection sensitivity across the (rect function) aperture, though the model allows for more complex aperture models, e.g., a trapezoidal function. 42 The distribution of secondary quanta computed at all possible locations in the x domain (taking y = 0 for simplicity) is shown in Fig. 1(C), where the probability distribution (vertical axis) is shown as an intensity map at each x location (horizontal axis) about the point of interaction.…”
Section: A a Cascaded Systems Model For Pcdsmentioning
confidence: 99%
“…͑34͒ should be replaced with trapezoids based on the research of Schumann and Lomheim. 50 Schumann and Lomheim have shown that lateral diffusion of photoelectrons is considerable when dealing with long wavelengths ͑Ͼ800 nm͒ of infrared light incident on the a-Si pixel layer. However, they have demonstrated that lateral diffusion is negligible when shorter wavelengths of visible light land on the pixel layer, such as the wavelengths generated by CsI:Tl in typical imaging systems.…”
Section: Discussionmentioning
confidence: 99%
“…• SR det (y k ) is the spatial response of the detector in y k domain (typically a boxcar with smoothed edges, whose width corresponds to the detector size) [20]. • W slit is a boxcar function corresponding to the slit width, the slit being the across-dimension of the diaphragm characterizing the instrument.…”
Section: The Icr Pre-filtering Blockmentioning
confidence: 99%